STRATEGI KEPEMIMPINAN BERBASIS PENGEMBANGAN MASYARAKAT UNTUK PENINGKATAN KUALITAS PEMBELAJARAN DI MTS SWASTA HASANUDDIN MEDAN - Indah Lestari (Jurnal Humaniora & Sosial Sains, 2025)
This study aims to examine the leadership strategy of the principal of MTs Swasta Hasanuddin Medan in improving the quality of learning. Through a qualitative approach, this study found that the principal used a facilitative strategy, involved teachers and staff in decision-making, and held regular discussions. The obstacles faced included time allocation due to two school locations and limited facilities and infrastructure. However, support from teachers and staff and monthly discussions had a positive impact. The results showed an increase in student learning outcomes, teacher creativity in utilizing resources, and community interest in the madrasah. These findings highlight the importance of participatory leadership and the role of organizational resources in supporting the success of an educational institution.